Striatal activity during reactive inhibition is related to the expectation of stop-signals. (11th October 2017) - Pas, Pascal; van den Munkhof, Hanna E.; du Plessis, Stéfan; Vink, Matthijs
Highlights: Striatal activation during reactive inhibition depends on expected stop signals. Striatal activation during reactive inhibition is not dependent on success. Less motor cortex activation is observed during unexpected versus expected stops. Abstract: Successful response inhibition relies on the suppression of motor cortex activity. The striatum has previously been linked to motor cortex suppression during the act of inhibition (reactive), but activation was also seen during anticipation of stop signals (proactive). More specifically, striatal activation increased with a higher stop probability. Using functional magnetic resonance imaging with specific regions of interest, we investigate for the first time whether activation in the striatum during reactive inhibition is related to previously formed expectations. We used a modified stop-signal response task in which subjects were asked trial by trial, after being presented a stop-signal probability cue, whether they actually expected a stop to occur. This enabled us to investigate the subjective expectation of a stop signal during each trial. We found that striatal activity during reactive inhibition was higher when subjects expected stop signals. These results help explain conflicting findings of previous studies on the association between striatal activation and inhibition, since we demonstrate a crucial role of the subjects' expectation of a stop signal and thus their ability to prepare for a stop in advance. In conclusion, the current results show for the first time that striatal contributions to reactive response inhibition are, in part, related to subjective anticipation.